Does multitasking improve the travel experience of public transport users? Investigating the activities during commuter travels in the Bandung Metropolitan Area, Indonesia - Rizki, M. (Springer Science and Business Media Deutschland GmbH, 2021)
This paper examines how different types of secondary activities, either offline or online, interact with travellersâ personal, travel, and spatial characteristics associated with the number of engaged secondary activities and commutersâ travel experience during a morning commute while using bus services of Trans Bandung Raya (TBR). By focusing on workers and students as productive groups of society and data collection in 2016, the results of this study found that activities with a high degree of attention and continuity in engagement will lead to a deactivation of other secondary activities during travel. While workers tend to deactivate other activities when they engage with social media or do online and offline socialising, students tend to have more active attention and continuity in engagements when they do online activities, particularly listening to music, engaging in social media, and playing games. Students in Indonesia tend to activate another secondary activities when they study on the bus such as reading a book or studying online using their gadgets. On the other hand, workers tend to undertake more activities while listening to music. Some results opposed with results from Europe and the US that collected the data in 2008â2012. In 2008â2012, the penetration effect might not be as massive as in 2016 and the types of online activites might not be as diverse as in 2016 which may make the results in Europe and the US different from this study. Different contexts among France, the Netherlands, Sweden, and Indonesia may let the results differ as well. In order to shift some potential travellers to use TBR, operators can promote the possibility of TBR as a platform to enhance workersâ travel experiences for working purposes and workersâ and studentsâ travel experiences for online socialising. However, TBR providers can alter travellers not to perform too many secondary activities during morning commutes in order to avoid peopleâs neutral experience. Providing more comfort space or facilities in the TBR might increase activities continuity during the trip, create relaxing conditions, and distract intense activity engagement. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.